2019
DOI: 10.17706/ijbbb.2019.9.2.100-108
|View full text |Cite
|
Sign up to set email alerts
|

Using Storytelling Robot for Supporting Autistic Children in Theory of Mind

Abstract: Autistic children have deficit in the understanding of how other people think and feel which is an important factor for social interaction and social communication. The understanding of how other people think and feel is called theory of mind. The storytelling activity could help the autistic children to learn about the theory of mind from the communication between the characters in the story stand point. This study investigated the use of BLISS robot with mobile application in the storytelling activity for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…In this regard, it has been observed that the social performance of autistic children improves when using a robot as a medium for social storytelling (Attawibulkul, Sornsuwonrangsee, Jutharee, & Kaewkamnerdpong, 2019;Vanderborght et al, 2012). The in-field experience showed that the autistic adolescents interacted with Vernie, saying "hello", saying "thank you", and directing the robot how to move in order to achieve a given task.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it has been observed that the social performance of autistic children improves when using a robot as a medium for social storytelling (Attawibulkul, Sornsuwonrangsee, Jutharee, & Kaewkamnerdpong, 2019;Vanderborght et al, 2012). The in-field experience showed that the autistic adolescents interacted with Vernie, saying "hello", saying "thank you", and directing the robot how to move in order to achieve a given task.…”
Section: Resultsmentioning
confidence: 99%
“…Membacakan buku cerita bergambar merupakan salah satu kegiatan yang dapat mengembangkan imajinasi dan kemampuan berbahasa anak, dan dapat membuat anak berpikir berdasarkan sudut pandang yang berbeda. Oleh karena itu, anak-anak dapat mempelajari theory of mind (teori pikiran) dan keterampilan sosial dari cerita tersebut (Attawibulkul et al, 2019). Dengan demikian, buku anak-anak dapat menjadi alat untuk mempromosikan pemahaman anak-anak tentang keadaan dalam diri dan orang lain (theory of mind) (Brophy-Herb et al, 2015;Rollo et al, 2017).…”
Section: Pendahuluanunclassified
“…Pemahaman tentang bagaimana orang lain berpikir, berkeinginan dan merasakan disebut theory of mind (Attawibulkul et al, 2019). Menurut penjabaran Sabbagh dan Bowman (2018), tom sering disebut sebagai teori karena meskipun seseorang tidak bisa melihat secara jelas emosi orang lain, anak mungkin mencoba dan telah mengira-ngira apa yang orang lain pikirkan berdasarkan berbagai bukti yang menjurus dengan dugaannya.…”
Section: Perkembangan Kemampuan Theory Of Mind Anak Usia Diniunclassified
“…According to Bharatharaj (2017), socialization skills are developed through interaction rather than being innate. Attawibulkul (2018) adds that self-confidence has a significant impact on socialization skills. People differ in their level of self-assurance.…”
Section: Hypothesis Testingmentioning
confidence: 99%